Temperature and Humidity Control Device In The Server Room PT.BFI Finance Tbk. Karawaci Based on Internet Of Things (IoT) - Misbahul Padli; Ika Dewi Lestari; Ramlan Ramlan; Irfan Nasrullah (Komunitas Dosen Indonesia, 2022)
The monitoring system for server room temperature and humidity at PT.BFI Finance which can increase the efficiency of electrical power using Arduino. At this time, technological advances are very fast, one of which is the presence of the Internet of Things, therefore the server room monitoring system at PT.BFI Finanace will use a temperature and humidity measuring device with an Arduino Uno microcontroller, Ethernet shield, Arduino Nano, buzzer, fan and the DHT22 sensor, which is able to overcome the weaknesses of existing server room monitoring. The purpose of this research is to make a temperature and humidity measuring device in the server room as a monitoring tool. The result of this research is a monitoring system for temperature and humidity conditions in the server room with a device whose temperature and humidity values ??will be stored in the MYSQL database, then displayed on a web application that will assist officers in monitoring the server room.